Metáforas e metonímias conceptuais em crônicas de Luis Fernando Veríssimo - Pinheiro, Cynthia Gomes (2015)
This work presents a description of the conceptual metaphors and metonymy recurrent in chronicles by Luis Fernando Verissimo, and the identification of possible inferences in understanding their metaphorical and metonymic linguistic expressions from the mental models. Therefore, we used as theoretical reference two theories: the Theory of Concept Metaphor and Metonymy (cf. Lakoff & Johnson, (1987, 2002 [1980], 2003 and others) and the Theory of Mental Models (cf. Van Dijk, (2012 [2008]). Our research, descriptive, consists of 31 chronicles present in the books Amor Veríssimo , Comédias da Vida Privada e Comédias da Vida Pública which show examples of situations we experience in two different and opposite contexts: private life and public life. First, we identified the metonymic and metaphorical linguistic expressions present in the texts. Then, we checked the metonymy and metaphor underlying these expressions. Finally, we investigated the possible inferences in understanding these linguistic expressions from the mental models. With the results, we confirmed our hypothesis that the updates of metaphors and metonymy portrayed in the investigated chronicles remit to mental models that lead to the understanding of the discursive aspects and hence the generation of the meaning of these chronicles.